Allosteric control of simian virus 40 T-antigen binding to viral origin DNA. - Vogt, B (1986)
Simian virus 40 (SV40) large tumor antigen (T antigen) possesses several biochemical activities localized in different domains of the protein. These activities include sequence-specific binding to two major sites, I and II, in the SV40 control region, ATPase, and nucleotide-binding activity. In the present communication, we present evidence that specific binding of immunopurified T antigen to SV40 DNA is markedly inhibited by low concentrations of ATP, dATP, GTP, and dGTP. The inhibition is reversible after removal of the nucleotide, suggesting that simple nucleotide binding rather than a covalent modification of T antigen in the presence of ATP is responsible for the inhibition. The results suggest that T antigen may assume two conformations, one active and one inactive in binding to the SV40 origin of replication. In the presence of purine nucleoside triphosphates, the inactive conformation is favored.